2021
DOI: 10.13057/nusbiosci/n130111
|View full text |Cite
|
Sign up to set email alerts
|

Review: Bioaccumulation of heavy metals in fish and other aquatic organisms from Karachi Coast, Pakistan

Abstract: Abstract. Yousif RA, Choudhary MI, Ahmed S, Ahmed Q. 2020. Review: Bioaccumulation of heavy metals in fish and other aquatic organisms from Karachi Coast, Pakistan. Nusantara Bioscience 13: 74-85. Heavy metals are being utilized in a variety of ways in industries, agriculture, food processing and household in many forms. Metals are unique environmental and industrial pollutants in the sense that they are neither created nor destroyed by human beings but are only transported and transformed into various product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Fidan et al [ 68 ] examined the contents of heavy metals in crucian carp muscles and noted the same order as in the current study. Yousif et al [ 69 ], based on the research of other investigators, observed that the elements were arranged in the following order: Fe > Zn > Cu > Mn. The findings included fish and other aquatic organisms from polluted areas (rivers and the Karachi Coast, Pakistan).…”
Section: Discussionmentioning
confidence: 99%
“…Fidan et al [ 68 ] examined the contents of heavy metals in crucian carp muscles and noted the same order as in the current study. Yousif et al [ 69 ], based on the research of other investigators, observed that the elements were arranged in the following order: Fe > Zn > Cu > Mn. The findings included fish and other aquatic organisms from polluted areas (rivers and the Karachi Coast, Pakistan).…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that fish from the northwestern coast of Egypt are relatively healthier than fish from other coasts on the Mediterranean either from the European or Arabian side due to lower heavy metal levels in their flesh, and Atlantic horse mackerel could promote it as a biomonitor for heavy metal pollution. Wong, 2000;Erdoğrul and Erbilir, 2007;Yousif et al, 2021). Normally heavy metals are present in water in low concentrations, but extensive anthropogenic activities lead to increase levels of metals in water to become toxic concentrations that are capable to accumulate causing damage to ecological system under certain environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Fish and seafood contain many contaminants, since anthropic activities (e.g., agriculture, industry, mining) increase their concentration in the aquatic ecosystem ( 17 , 41 43 ). Clearly, because of biomagnification, pollutants are mostly concentrated in the longer-living and larger predatory fish species such as swordfish, tuna, and shark.…”
Section: The Bad Face Of Janusmentioning
confidence: 99%